The Effect of Almanar School on the Directions if Interpretation and it's Disciplines at The Time of Alsayed Raseed Ridha - Egypt as a Model – (Damascus University Journal for legal sciences, 2024)
The research sheds light on the directions and disciplines of interpretation that emerged in the XIV Hijri century, that were unique with their modernization, as Almanar interpretation had emerged at the time, by Alsayed Mohammad Rasheed Ridha, The research presented a brief introduction of Almanar School, and the biography of it's author, and a general presentation of his time, then differentiated between the terms Direction and Discipline,  and identified the main modernizing directions of his time: the "Guidance", "Scientific", and "Literary" Directions, and what is know as "Off Interpretations", had emerged, and under each direction, three disciplines are listed: Placement Oriented (Classic), Subject Oriented, and Interpretational Essay disciplines, and research has shown the relation of Almanar's school with these directions and it's position regarding them, and that the boarders between them are not distinct, and that these directions intersect with each other.
Keywords: Directions; Disciplines; Guidance; Scientific; Literary; Off Interpretations; Placement Oriented; Subject Oriented; Interpretational Essay.